Storage studies of chilli (Capsicum annuum L) cultivars on germination and vigour index - P Venkata Reddy, C Ravi Shankar, K Uma Jyothi, S Surya Kumari (Journal of Spices and Aromatic Crops, 2008)
The experiment was conducted at the Chillies Improvement Project, Regional AgriculturalResearch Station, Lam, Guntur and in the Priyanka Cold Store, Chilakaluripet Road, Gunturduring the year 2001-2002. The fresh ripe chilli cultivars viz: LCA 334, LCA 357, LCA 206,LCA 235, Paprika type, Guntur Grand and Wonder Hot were collected and Sun dried bothmoisture lend of 10-11 per cent. Then the dried chilli was packed in gunny bags in two sets.One set was kept in cold store and the other set at ambient condition. Samples were drawnat monthly intervals and subjected to seed germination and seedling vigour index. Theseeds of cultivars LCA 235, LCA 206, LCA 334 and LCA 357 recorded higher germinationpercentage and vigour index at different intervals of storage. The chilli stored in cold storeproved superior to ambient storage even for good quality seed.